Energy flexibility scenarios for North Macedonia - Zaev, Emil; Babunski, Darko; Lazarevikj, Marija; Koleva, Radmila (International Association for Hydro-Environment Engineering and Research (IAHR), 2022)
The Paris Agreement signed in 2015, unites nearly 200 countries on the goal of limiting global warming and lowering carbon emissions. The goal of lowering carbon emissions can mainly be achieved by lowering fossil fuels within the energy sector since their use in electricity generation is a significant contributor to greenhouse gas emissions. This is why European countries, as well as North Macedonia, are planning to reduce the amount of climate-damaging fossil-fueled power plants, but to cover electricity demand, the share of renewable energies (in North Macedonia mostly wind and solar energy, here addressed as intermittent renewable energy sources - IRES) within their power systems must be increased. Changing power systems and including higher shares of IRES will increase imbalances and thus the need for flexibility (refers to means able to balance electricity supply and demand). Imbalances have always occurred in power systems, resulting from various reasons, and power systems are able to react with flexibility. Considered options, categorized into four kinds of flexibility (dispatchable generation, demand side management, increased interconnection, and energy storage), all offer possibilities to balance the systems by different approaches. Although all providing individual advantages, hydropower, especially pumped storage hydropower, was identified in this paper to be a very flexible, diverse option and a technology capable of meeting flexibility challenges set by the increase of IRES. The need for flexibility in the hydropower production could be improved using variable-speed turbines instead of multiple start-stops depending on the grid demand.
Keywords: Hydro power plants; Flexibility scenarios; Power systems; Variable-speed turbines